2016
DOI: 10.1002/gps.4518
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in relation to independency in older, comorbid stroke patients in a stroke unit

Abstract: From a clinical point of view, we suggest combining physical and cognitive training from the very early phase of recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…However, regression analyses model including MoCA's cognitive domains showed low sensitivity and specificity. The results are partially in line with other studies showing that cognitive domains like attention, language (29), executive functions, and delayed reproduction (6) might have an impact on ADLs, highlighting executive functions as the most important. Decline in executive and memory functions is usually related to age (30).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, regression analyses model including MoCA's cognitive domains showed low sensitivity and specificity. The results are partially in line with other studies showing that cognitive domains like attention, language (29), executive functions, and delayed reproduction (6) might have an impact on ADLs, highlighting executive functions as the most important. Decline in executive and memory functions is usually related to age (30).…”
Section: Discussionsupporting
confidence: 91%
“…However, in that study cognitive function was not identified as a significant variable. In contrast, cognitive functions assessed with a different cognitive tool was associated with ADL dependence (6). Cognitive malfunctioning is known to be related to older age (33, 34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ICH is associated with motor damage [ 25 , 26 ] and cognitive impairments [ 27 ] that may be closely related to oxidative stress [ 28 ]. Our current results show that ICH generates locomotor and exploratory damage (OF), which is maintained for up to 3 days after injury.…”
Section: Discussionmentioning
confidence: 99%